Análise dos casos de leishmaniose tegumentar americana no município de Belo Horizonte, notificados entre 2001 e 2008, com ênfase na forma mucosa - Rodrigo Santana Fantauzzi (2009)
The present study evaluated the notified cases of tegumentary leishmaniasis in the city of Belo Horizonte, Brazil, with emphasis in the mucous form, focusing on the otorhinolaryngologycal follow-up after specific treatment. The data-base from the Health Council of Belo Horizonte was carried out regarding the cases of American Tegumentary Leishmaniasis in both types cutaneous and mucous forms notified between 2001 and 2008, as well as a clinical assessment of the mucous cases. Out of 745 patients notified, 539 (72%) presented the skin-type, 137 (18%) the mucous-type, and 69 (9%) unidentified types. Contact was tried with the 58 patients with the mucous form who lived in Belo Horizonte. However, incorrect data on their notification cards allowed effective contact with only nine of them, who had been treated with pentavalent antimony at least one year previously. Out of these nine patients, four had been treated five years before, three, between five and ten years before, and two over ten years before. All of them underwent an otolaryngological exam as part of the present study. Nasal endoscopy and biopsy confirmed recurrence in three of the nine assessed cases. In these three cases, the diagnosis was possible due exclusively to the active research done in the current study. In conclusion, the cases of mucous leishmaniasis in Belo Horizonte were not properly notified. The recurrences of the mucous form previously treated with pentavalent antimony occurred more frequently after the first year of treatment. Regular post-treatment monitoring should be adopted in the centers of such zoonosis not only in the first year, as determined by the Health Ministry, but also afterwards. It is suggested a period of at least another four years, taking into account the late recurrences pointed out by this study.